Financial Performance Of Indian Cement Industry With Reference To Select Cement Companies – A study - Sardar Jaswanth Singh; Professor Madhuri Puranik (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Cement Industry play very significant role in Indian economy. It facilitates the basic infrastructure facility for the development of the country. The companies selected for this study are taken on the basis of their current market share and according to the availability of data. The financial year of this study is from April to March. The data for the study is taken for five years i.e. 2018-19 to 2022-23. Ultratech Cements, JK Cements, Ambuja Cements, ACC and Ramco are selected for this study. The study applied various ratio analysis for the understanding the financial performance of the selected companies. The study highlighted that current ratio, quick ratio and Net Profit ratio is good for ACC when compared to the other companies under study which stated that ACC earns more net profit than other companies and it is more efficient in converting its sales into actual profit. The study found that absolute liquid ratio is good for Ramco when compared with other companies and Ambuja Cements earned more gross profit than other companies and it can make reasonable profit on sales, as long as it keeps overhead costs in control. JK Cements earns more operating profit than other companies and it shows that the company is more efficient in controlling the cost and expenses associated with the business operations, profit generated by the company with the money invested by the shareholders and had more investment made in the business for long term.